2016
DOI: 10.5688/ajpe80341
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of an Explicit Critical-Thinking Curriculum to Improve Pharmacy Students’ Critical-Thinking Skills

Abstract: Objective. The Health Sciences Reasoning Test (HSRT) is a validated instrument to assess criticalthinking skills. The objective of this study was to determine if HSRT results improved in second-year student pharmacists after exposure to an explicit curriculum designed to develop critical-thinking skills. Methods. In December 2012, the HSRT was administered to students who were in their first year of pharmacy school. Starting in August 2013, students attended a 16-week laboratory curriculum using simulation, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
0
21
1
1
Order By: Relevance
“…All these studies 4,5,10,11,18 supported the value of the HSRT to measure changes in critical thinking skills. The methodologies in these studies are similar, but the noviceexpert method used by Hanlon et al 10 and Huhn et al 11 identified differences in critical thinking skills of novice students compared to an expert cohort.…”
Section: Methodologies To Describe Evaluation Of Critical Thinkingmentioning
confidence: 77%
See 1 more Smart Citation
“…All these studies 4,5,10,11,18 supported the value of the HSRT to measure changes in critical thinking skills. The methodologies in these studies are similar, but the noviceexpert method used by Hanlon et al 10 and Huhn et al 11 identified differences in critical thinking skills of novice students compared to an expert cohort.…”
Section: Methodologies To Describe Evaluation Of Critical Thinkingmentioning
confidence: 77%
“…According to both Huhn et al 11 and Hanlon et al, 10 construct validity of the HSRT was supported by their findings, and the HSRT was a reliable tool to ascertain differences in critical thinking skills of novice and expert clinicians. While these studies explored critical thinking abilities of physical therapy and dental students, other studies by Nornoo et al 5 and Cone et al 18 used the HSRT to evaluate changes in pharmacy students' critical thinking skills at various points in their education. They found the HSRT was a valid tool to identify changes in critical thinking skills of pharmacy students over a short period.…”
Section: Methodologies To Describe Evaluation Of Critical Thinkingmentioning
confidence: 99%
“…13 Students learn and improve their critical thinking skills with courses that include explicit and focused education targeting these skills. 14,15 Five basic approaches to decision-making and problem-solving approaches in pharmacy education have been identified: clinical, ethical, managerial, economic, and legal. 15 The clinical approach was one focus of the pharmacotherapy capstone course, but ethical and economic approaches were also included.…”
Section: Discussionmentioning
confidence: 99%
“…These articles describe the implementation process and study design challenges, which varied depending on whether the assessment tool was developed for use with undergraduates or specific to health care practice. 43,44 Educational activities aimed at improving broad critical-thinking skills may indirectly benefit the development of future pharmacy entrepreneurs, but no direct link has been demonstrated between pharmacy students' performance on critical thinking assessments and long-term entrepreneurial outcomes. 4,18,[32][33][34]19,20,23,24,[26][27][28][29] Entrepreneurship identified with innovation, creativity, and new opportunities.…”
Section: Critical Thinkingmentioning
confidence: 99%